2006
DOI: 10.1002/ijc.22083
|View full text |Cite
|
Sign up to set email alerts
|

The expression levels of the transcriptional regulators p300 and CtBP modulate the correlations between SNAIL, ZEB1, E‐cadherin and vitamin D receptor in human colon carcinomas

Abstract: ZEB1 and SNAIL repress CDH1 and induce epithelial-mesenchymal transition (EMT). However, SNAIL and ZEB1 also activate or regulate other target genes in different ways. For instance, vitamin D receptor (VDR), which activates CDH1 expression upon ligand binding, is repressed by SNAIL but induced by ZEB1. We examined whether the biological activity of SNAIL and ZEB1 in colon cancer is regulated by interacting cofactors. The mRNA expression levels of SNAIL and ZEB1, and of transcriptional regulators p300 and CtBP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 40 publications
(67 reference statements)
4
93
0
1
Order By: Relevance
“…In addition to the low number of tumors analyzed, other factors might account for this lack of total correlation between the expression of the NAT/5Ј-UTR intron (and presumably Zeb2 protein) and the loss of E-cadherin; for instance, Zeb1 might be also contributing to E-cadherin down-regulation. Alternatively, repression by Zeb2 might be also dependent on the levels of the transcriptional regulators p300 and CtBP, which modulate the inverse correlation between Zeb1 and E-cadherin (Peña et al 2006). In any case, these analyses suggest that maintenance of the 5Ј-UTR intron is probably the consequence of increased transcription of the Zeb2 NAT in human tumors and further underline the relevance of our findings.…”
Section: An Antisense Transcript Regulates Zeb2 Expression Genes and Desupporting
confidence: 65%
“…In addition to the low number of tumors analyzed, other factors might account for this lack of total correlation between the expression of the NAT/5Ј-UTR intron (and presumably Zeb2 protein) and the loss of E-cadherin; for instance, Zeb1 might be also contributing to E-cadherin down-regulation. Alternatively, repression by Zeb2 might be also dependent on the levels of the transcriptional regulators p300 and CtBP, which modulate the inverse correlation between Zeb1 and E-cadherin (Peña et al 2006). In any case, these analyses suggest that maintenance of the 5Ј-UTR intron is probably the consequence of increased transcription of the Zeb2 NAT in human tumors and further underline the relevance of our findings.…”
Section: An Antisense Transcript Regulates Zeb2 Expression Genes and Desupporting
confidence: 65%
“…CTBP is part of the corepressor complex, CoREST and is involved in repression of tumor suppressor genes such as CDH1 (encoding E-cadherin), PTEN, and CDKN2A (37)(38)(39)(40)(41). In the present study, we found that suppression of Ctbp2, but not of Ctbp1, confers RA resistance, suggesting the unique attribute of Ctbp2 as a coactivator in RA signaling (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…It should also be remarked that transfection of ZEB1 into SW620 colon carcinoma cells results in the upregulation of endogenous VDR (Lazarova et al, 2001). In fact, we earlier observed an inverse correlation between ZEB1 and CDH1 expression in tumor tissue when the cofactor CtBP was overexpressed and a stronger direct correlation between ZEB1 and VDR when the cofactor p300 was overexpressed (Pena et al, 2006). In summary, the regulation of CDH1 and VDR seems to be different in tumor and NAT.…”
Section: Adh-gfp Adh-sn Row Column Cytokine Cytokinefull Name Median mentioning
confidence: 75%